Near wellbore remediation for organic impaired reservoir using a thermo-chemical system - Rajindar Singh, Jasvinder Singh (2017)
The Sirikit oilfield, situated some 400 km N of Bangkok, Thailand, is a fault-bounded structure within a major half-graben basin, comprising relatively 8 km thick basin-fill succession includes alluvial fan-fluvial deposits overlain by the fluvio-deltaic Lan Krabu Formation, which contains two main oil reservoirs. Based on the production trend obtained, it can be clearly seen that there was significant decline from the wells. This may be due to organic deposits in tubing and near wellbore which causes blockage. This was proved from the SARA analysis carried out in the laboratory. SARA analysis separates the crude oil into four major fractions: saturates (including waxes), aromatics, resins and asphaltene (SARA). This separation is based on the solubility and polarity of these components. This method of characterizing crude oil is done by separating it into smaller fractions, each of which has a different composition from the rest and various solubility to solvents. The tested sample was predominantly rich in macro crystalline wax (low molecular weight) along with of micro crystalline wax (high molecular weight, high melting point) and asphaltene. Agglomeration of wax along with asphaltene and naphthenate are expected around well bore and tubular. Thermo-Chemical System is a technology whereby a two pack chemical is used to dissolve and disperse organic solid depositions in production well tubing’s and wellbores to enhance the oil production from wells by generating exothermic heat up to 200°C and efficient surfactant, ester. Modular pumping technology is applied to deliver the active chemical to target location, in production tubing and 2 feet near wellbore remediation.